Kir2.1-Nav1.5 Channel Complexes Are Differently Regulated than Kir2.1 and Nav1.5 Channels Alone - Utrilla, Raquel G.; Nieto-Marín, Paloma; Alfayate, Silvia; Tinaquero, David; Matamoros, Marcos; Pérez-Hernández, Marta; Sacristán, Sandra; Ondo, Lorena; de Andrés, Raquel; Díez-Guerra, F. Javier; Tamargo, Juan; Delpón, Eva; et al. (Frontiers in Physiology, 2017)
Cardiac Kir2.1 and Nav1.5 channels generate the inward rectifier K+ (IK1) and the Na+ (INa) currents, respectively. There is a mutual interplay between ventricular INa and IK1 densities, because Nav1.5 and Kir2.1 channels exhibit positive reciprocal modulation. Here we compared some of the biological properties of Nav1.5 and Kir2.1 channels when they are expressed together or separately to get further insights regarding their putative interaction. First we demonstrated by proximity ligation assays that in the membrane of ventricular myocytes Nav1.5 and Kir2.1 proteins are in close proximity to each other (<40 nm apart). Furthermore, intracellular dialysis with anti-Nav1.5 and anti-Kir2.1 antibodies suggested that these channels form complexes. Patch-clamp experiments in heterologous systems demonstrated that the inhibition of the Ca/calmodulin-dependent protein kinase II (CaMKII) decreased the INa and IK1 generated by Nav1.5 and Kir2.1 channels when they were coexpressed, but not the IK1 generated by Kir2.1 channels alone, suggesting that complexes, but not Kir2.1 channels, are a substrate of CaMKII. Furthermore, inhibition of CaMKII precluded the interaction between Nav1.5 and Kir2.1 channels. Inhibition of 14-3-3 proteins did not modify the INa and IK1 densities generated by each channel separately, whereas it decreased the INa and IK1 generated when they were coexpressed. However, inhibition of 14-3-3 protein did not abolish the Nav1.5-Kir2.1 interaction. Inhibition of dynamin-dependent endocytosis reduced the internalization of Kir2.1 but not of Nav1.5 or Kir2.1-Nav1.5 complexes. Inhibition of cytoskeleton-dependent vesicular trafficking via the dynein/dynactin motor increased the IK1, but reduced the INa, thus suggesting that the dynein/dynactin motor is preferentially involved in the backward and forward traffic of Kir2.1 and Nav1.5, respectively. Conversely, the dynein/dynactin motor participated in the forward movement of Kir2.1-Nav1.5 complexes. Ubiquitination by Nedd4-2 ubiquitin-protein ligase promoted the Nav1.5 degradation by the proteasome, but not that of Kir2.1 channels. Importantly, the Kir2.1-Nav1.5 complexes were degraded following this route as demonstrated by the overexpression of Nedd4-2 and the inhibition of the proteasome with MG132. These results suggested that Kir2.1 and Nav1.5 channels closely interact with each other leading to the formation of a pool of complexed channels whose biology is similar to that of the Nav1.5 channels.